Efektivitas Strategi Pemasaran Digital Terintegrasi dalam Meningkatkan Daya Saing Kelompok Usaha Berbasis Komunitas pada Kelompok Usaha Alga Lestari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the effectiveness of an integrated digital marketing strategy in improving the competitiveness of a community-based business group, namely the Alga Lestari Business Group. The study is motivated by limited market access, low digital literacy, and weak institutional readiness commonly faced by community-based micro and small enterprises, despite the increasing importance of digital marketing. This research aims to examine changes in business competitiveness following the implementation of structured digital marketing training and assistance. A quantitative explanatory approach was applied using a pre-test and post-test design. Data were collected through structured questionnaires administered to all group members before and after the intervention and analyzed using descriptive statistical methods. The findings reveal a significant improvement across all measured indicators. The average level of participants’ understanding increased from 27% in the pre-test to 81% in the post-test, representing an overall improvement of 54%. The most substantial increase occurred in the ability to create and manage digital business accounts, which rose from 20% to 78%. Improvements were also evident in marketing network identification, business legality awareness, and product packaging and labeling design, each showing increases of approximately 55%. Meanwhile, improvements in branding and promotional strategies were relatively lower, indicating the need for continued assistance. These results demonstrate that an integrated digital marketing strategy supported by legal readiness, branding consistency, and marketing networks effectively enhances the competitiveness of community-based enterprises. The study contributes theoretically and practically by offering an evidence-based model for strengthening digital marketing capacity among community-based business groups.